Comparison of the Postoperative Liver Function Between Total Intravenous Anesthesia and Inhalation Anesthesia in Patients with Preoperatively Elevated Liver Transaminase Levels: A Retrospective Cohort Study - Oh SK; Lim BG; Kim YS; Kim SS (Dove Medical Press, 2020)
Seok Kyeong Oh, Byung Gun Lim, Young Sung Kim, Seong Shin Kim Department of Anesthesiology and Pain Medicine, Korea University Guro Hospital, Korea University College of Medicine, Seoul, Republic of KoreaCorrespondence: Byung Gun Lim Email bglim9205@korea.ac.krBackground: Anesthesia and surgery may deteriorate liver function in patients with elevated liver enzyme levels; therefore, in these patients, choosing anesthetics with less hepatotoxicity is important.Methods: This retrospective study investigated the effect of total intravenous anesthesia (TIVA) versus inhalation anesthesia (INHA) on the postoperative liver function in patients with preoperatively elevated liver enzyme levels (aspartate transaminase [AST] or alanine transaminase [ALT] > 40 U/L) who underwent non-hepatic surgery under general anesthesia. We compared the changes in enzyme levels within 24 hrs before and after surgery.Results: In 730 patients (TIVA: n=138; INHA: n=592), the baseline characteristics were comparable, except for higher comorbidity rates in the TIVA group. The median anesthesia and operation times were significantly longer in the TIVA group because approximately 50% of the TIVA group (vs 19.7% of the INHA group) underwent neurosurgery, which had a relatively longer operation time than other surgeries. Intraoperative hypotensive events and vasopressor use were more frequent in the TIVA group. After 1:4 propensity score matching (TIVA: n=94; INHA: n=376), the baseline characteristics and surgical variables were comparable, except for longer anesthesia time. Before matching, postoperative AST and ALT changes were significantly lower in the TIVA group than in the INHA group. After matching, only the ALT change was significantly lower after TIVA than after INHA [median (interquartile range), − 16.7 (− 32 to − 4) % vs − 12.0 (− 28.6– 6.5) %, P=0.025].Conclusion: TIVA may be safer for patients with preoperatively elevated liver transaminase levels.Keywords: alanine transaminase, aspartate transaminase, intravenous anesthetics, inhalation anesthetics, chemical and drug-induced liver injury